Evolução do uso abusivo de derivados de ópio - Pereira, Mariana de Moura (2016)
Opium is a substance extracted from a plant that belongs to the Papaveraceae family, known popularly as poppy. The name has Greek origin and its nomenclature varies according to provenance, being opiates for natural and some semi-synthetic substances and opioids for synthetic. They act as agonists of specific presynaptic or postsynaptic opioid receptors, located generally in the central nervous system and peripheral system. It is estimated that there are between 12 and 21 million opioid users worldwide and recently some European countries and the United States reached epidemiological levels of consumption. Usually opium derivatives are used as a drug of recreation or as medication for treatment of pain and may cause irreparable damage when used in excess. Thus, the administration, the dose and its frequency should be watched carefully, avoiding undesirable side effects. The aim of this paper is to present the complications arising from the use of these substances, as well as providing information and establish consumption parameters in Brazil and other countries. As it is a topic of concern for public health, it is necessary to encourage further clinical and epidemiological research.